Launch Environmental Test for KITSAT-3 FM - Sang-Hyun Lee; Young-Soon Jang; Jeong-Seok Bae; Dong-Woo Lee; Yun-Hwang Jung; Dan-Keun Sung (Journal of Astronomy and Space Sciences, 1999)
The satellite experiences the severe launch environment such as vibration, acceleration, shock, and acoustics induced by rocket. Therefore, the satellite should be designed and manufactured to endure such severe launch environments. In this paper, we describe the structure of the KITSAT-3 FM(Flight Model) and the processes and results of the launch environmental test to ensure the reliability during launch period.